PENGARUH KEGIATAN MENANAM TANAMAN OBAT TERHADAP SIKAP ILMIAH ANAK USIA 5-6 TAHUN DI PAUD SYAUQIA MUSIRA KID - Suzhi Sahna Pramesty; Peny Husna Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Scientific attitude is an important aspect that needs to be stimulated in early childhood because it supports children in developing curiosity, confidence, problem solving skills, and positive responses during the learning process. Based on initial observations conducted at PAUD Syauqia Musfira Kids Tanjung Morawa, children’s scientific attitude still required further stimulation, while science learning activities carried out in school had not been routinely implemented through direct environmental-based experiences. This study aimed to determine the effect of medicinal plant planting activities on the scientific attitude of children aged 5–6 years. This research used a quantitative approach with a pre-experimental design in the form of one group pretest-posttest design. The subjects of this study were children aged 5–6 years at PAUD Syauqia Musfira Kid Tanjung Morawa. Data collection was carried out through observation using indicators of scientific attitude consisting of curiosity, skepticism, positive approach to failure, and positive self image. Data analysis was conducted using the Wilcoxon Signed Rank Test with SPSS. The results showed that the average pretest score was 19.92 in the Belum Berkembang (BB) category, while the average posttest score increased to 33.31 in the Berkembang Sesuai Harapan (BSH) category. Hypothesis testing showed a significance value of 0.001 < 0.05, indicating that medicinal plant planting activities had a significant effect on the scientific attitude of children aged 5–6 years.